Productive response to two concentrate allocation strategies in dairy cows grazing with restricted pasture allowance - Bretschneider, Gustavo (2019)
The objective of this study was to compare the effects of two concentrate allotment strategies on the performance of dairy cows grazing on restricted pasture and supplemented with conserved forage. Dairy cows fed equal amounts of concentrate (fixed daily rate: 5.5 kg DM/cow) were compared to cows supplemented with concentrate according to their lactation stage as follows: 10.0, 5.0, and 1.5 kg DM/cow daily during early, mid, and late lactation, respectively (average daily dose: 5.5 kg DM/cow). There was a supplementation strategy × lactation stage interaction (P < 0.05) for energy-corrected milk (ECM). For early lactation cows, supplementation at a variable rate increased ECM yield by 14.61% (P < 0.05). There was a supplementation strategy × lactation stage interaction (P < 0.05) for body weight change. At late lactation stage, cows supplemented at a fixed rate gained weight (+ 0.16 kg/day), whereas those supplemented at a variable rate lost weight (– 0.08 kg/day; P < 0.05). No significant effect was found for body condition score. The prioritization of milk production rather than the attenuation of body reserve mobilization suggests that concentrate allowance based on lactation stage may be unsuitable for minimizing the negative energy balance in early lactation cows.